T Regulatory cells from non-obese diabetic mice show low responsiveness to IL-2 stimulation and exhibit differential expression of anergy-related and ubiquitination factors - Godoy, Gloria J. (2019)
Fil: Godoy, Gloria J. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Bioquímica Clínica, Argentina.